Distinct glycosylation and functional profile of typhoid vaccine-induced antibodies in a UK challenge study and Nepalese children - Stockdale, L. K.; de Haan, N.; Hill, J.; Johnson, M.; Tomic, A.; Wuhrer, M.; Jones, E.; Jin, C.; Nouta, J.; Koeleman, C. A. M.; Verheul, M.; Basnyat, B.; et al. (Frontiers in Analytical Science, 2022)
Vaccines against typhoid fever have been shown to be safe and effective in field trials. The mechanism through which the vaccines protect remains elusive. Recent data have implicated antibody glycosylation, and specifically afucosylated antibodies, as an important factor in vaccine-induced effector function for a range of viral infections, however this has not been evaluated for vaccines against bacterial infections such as Salmonella typhi. Here, we studied antibody glycosylation after either Vi-conjugate or Vi-polysaccharide vaccine in a UK cohort who were then challenged with virulent S. typhi, and compared findings to antibody glycosylation after Vi-conjugate vaccine in Nepalese children living in a typhoid endemic region. We compared vaccine-induced responses and correlated these measures with antibody-dependent function. Robust antigen-specific antibody galactosylation and sialylation modifications were induced by both vaccines in UK adults, with Vi-conjugate vaccine inducing Vi-specific glycan changes of higher magnitude than Vi-polysaccharide. Among those individuals diagnosed with typhoid fever after challenge, a distinct glycan profile was correlated with disease severity. Elevated galactosylation and sialylation was correlated with increased antibody-dependent phagocytosis by macrophages and neutrophils among UK adults. While bulk IgG glycosylation differed between Nepalese children and UK adults, vaccination with the Vi-conjugate vaccine overcame these differences to result in similar Vi-specific antibody glycosylation profiles 28 days after vaccination in both cohorts.